DETERMINATION OF OPTIMAL RATES FOR ELECTRICITY GENERATION IN- SYSTEM I TERCONECTADO FROM WASTE BIOMASS, USING THE RETSCREEN SOFTWARE AND APPLICATIONS OF RAPID APPRAISAL BEFS PROJECT UN FOOD AND AGRICULTURE (FAO) - Delgado Acevedo, Aldo Max (2014)
Peru has a surface of 82’369,713 hectares of forestry suitability, 7’600,000 hectares with agriculture farming capacity and a biomass potential for energy generation estimated in 272 million annual metric tons [2]. For energy generation scope, there are four categories: bioenergy crops, agriculture waste, livestock waste and urban solid waste. Gasification technology would be more convenient for the scope of the study. Assessing the theoretical potential of energy generation with biomass for grid connection, the result was the identification of two sources: Rice (Cajamarca, Lambayeque and Piura) and sugar cane (Lambayeque, Piura and Lima).With the aim to design the energy demand, the Electricity Referential Plan 2008 – 2017 was used as base document. The considered assumptions were the following: Medium growth scenario: Annual growth rate 7.55%; Optimist growth scenario: Annual growth rate 8.7%; Conservative growth scenario: Annual growth rate 6.36%. In order to determine the energy potential by regions disaggregated by projects, it was used the application FAO BEFS Rapid Appraisal and the software RETScreen. From the 17 analyzed projects, the tools calculated that only four could be part of a viable Project portfolio: Agroindustria Paramonga, Agroindustria Caña Brava, Huaycoloro Landfill and Gran Mercado Mayorista de Lima (Santa Anita). The main barrier found is that the top tariffs established by the Government in the last bids are even near to the optimum tariffs analyzed in this study.